Horse Bridle of the Sсythians of Pryinhullia - Mogylov, Oleksandr; Kirieiev, Oleh; Shyshka, Ruslan (Revista Arheologică, 2026)
The article is devoted to the study of equestrian burials and horse equipment of the Scythian tribes that inhabited the basins of the Inhulets and Inhul rivers in the Northern Black Sea region. The burial rites associated with barrows are examined, and the structural features of their mounds are clarified. The presence of moats around the the mounds, crepids, Scythian stone statues, and fire-related rituals is noted. The grave types include pits, catacombs, and wooden tombs. Horse burials, the types of horse graves, methods of laying the animals, and associated finds are analysed. The assemblage of horse equipment comprises bits, cheek-pieces, plates, frontlets, buckles, tubes, nahrapnyks, and whips. It has been established that only bronze bits are known in the region from the Early Scythian period. All currently identified mounds containing horse burials and bridle elements date to the 5th-4th centuries BC and belonged to male warriors. The presence of such burial mounds in the region indicates the spread of equestrian culture during the Scythian period. Horsemen formed the core of the Scythian army, while advanced sets of horse equipment and weapons ensured high mobility and a developed level of military skill.